Low-temperature-processed ZnO–SnO2 nanocomposite for efficient planar perovskite solar cells - Song, Jiaxing; Zheng, Enqiang; Wang, Xiao-Feng; Tian, Wenjing; Miyasaka, Tsutomu (Solar energy materials and solar cells, 2016)
Electron collection layer (ECL) is one of the most important fundamentals to determine the power conversion efficiency (PCE) in organometal halide-based perovskite solar cells (PSCs). Herein, we prepared ZnO–SnO2 nanocomposites with different Zn/Sn ratios at low temperature as ECLs for CH3NH3PbI3-based planar-structured PSCs. ZnO–SnO2 nanocomposite with the optimal ~89mol% of the ZnO content gives higher PCE than the ZnO for the best fabricated PSC. The photoluminescence spectroscopies measured in both steady and transient states and the electrochemical impedance spectroscopy were carried out to characterize the interface of CH3NH3PbI3 and different ECLs, namely ZnO, ZnO–SnO2 composite, and SnO2. The high PCE of PSCs based on the ZnO–SnO2 nanocomposite ECL was thus attributed to joint contributions of the high charge extraction efficiency and large charge recombination resistance both on the CH3NH3PbI3/ECL interface. The thermal stability of CH3NH3PbI3 absorber and the device stability of the corresponding PSC are both dependent on the ECLs in the order: SnO2>ZnO–SnO2 >ZnO, suggesting that the hydroxyl-induced degradation of CH3NH3PbI3 may be predominant in the ambient air environment in the initial ~700h. The PCE of the optimized device was further improved to 15.2% by introducing the low-temperature processable Al2O3 as a capping layer to the ZnO–SnO2 composite. [Display omitted] •The first report on ZnO–SnO2 as electron collection layer for perovskite solar cell.•The ZnO–SnO2 electron collection layers are low-temperature-processed.•An optimal ZnO–SnO2 (2:1 weight ratio in solution) gives the relatively high PCE.•The ZnO–SnO2 thin films exhibit better thermal stability of CH3NH3PbI3.•The PCE of the optimized device was further improved by introducing the Al2O3 layer.